Gaya Kepemimpinan Transformasional, Lingkungan Kerja Non Fisik dan Kualitas Kehidupan Kerja terhadap Kinerja Pegawai Balai Monitor Spektrum Frekuensi Radio Kelas II Manado - Takaliuang, Stenly; Shine P. Siolemba; Sri Harijati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to examine the partial and simultaneous relationships between transformational leadership style, non-physical work environment, and quality of work life on employee performance at the Class II Manado Radio Frequency Spectrum Monitoring Center. The population in this study consists of all employees at the Class II Manado Radio Frequency Spectrum Monitoring Center, with a sample of 52 employees taken using the simple random sampling technique. The data collection technique used a questionnaire that has been declared valid and reliable. The data analysis used in this study is multiple regression analysis, with the analysis assisted by SPSS software. Based on the results of the data analysis, it was concluded that there is a significant influence between transformational leadership style, non-physical work environment, and quality of work life on employee performance both partially and simultaneously. In addition, it was also found that the influence of these three variables on employee performance is 78.5%. This means that the influence of these three variables falls into the strong category. The remaining 21.5% is influenced by other variables that were not examined in this study. The implication of this research is that to improve employee performance, the head of the Class II Manado Radio Frequency Spectrum Monitoring Center needs to implement a transformational leadership style, as well as pay attention to non-physical work environment aspects and enhance the quality of employees' work life. Keywords: Transformational Leadership Style, Non-Physical Work Environment, Quality Of Work Life, Employee Performance